2003
DOI: 10.1093/geront/43.2.203
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Social Cognition in Frail Older Adults and Its Association With SocialFunctioning in the Nursing Home

Abstract: Measures of social cognition assess a domain of functioning that is not evaluated by traditional tests of cognitive status. These measures are informative about frail, older adults' ability to understand and respond to others and could be used to predict patterns of social functioning in nursing homes and other naturalistic settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Its positive association with activity level provides significant support to the barrier (rather than compensation) proposition. Mental health impairments can harm aging adults’ sense of surroundings and inner behavioral motivation mechanisms to enter social contexts for activity participation [41]. As interpersonal barriers, limitations in mental strength, mood, and cognition can dramatically reduce a person’s capacity and intention to participate in activities [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its positive association with activity level provides significant support to the barrier (rather than compensation) proposition. Mental health impairments can harm aging adults’ sense of surroundings and inner behavioral motivation mechanisms to enter social contexts for activity participation [41]. As interpersonal barriers, limitations in mental strength, mood, and cognition can dramatically reduce a person’s capacity and intention to participate in activities [41].…”
Section: Discussionmentioning
confidence: 99%
“…Mental health impairments can harm aging adults’ sense of surroundings and inner behavioral motivation mechanisms to enter social contexts for activity participation [41]. As interpersonal barriers, limitations in mental strength, mood, and cognition can dramatically reduce a person’s capacity and intention to participate in activities [41]. Social stigma and discrimination associated with mental illness can also represent interpersonal barriers and isolate people from activities [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social causation hypothesizes that better social support ( Seeman, Lusignolo, Albert, & Berkman, 2001 ) and larger social networks ( Béland, Zunzunegui, Alvarado, Otero, & Del Ser, 2005 ) retard cognitive decline, aligned with social integration theory reviewed by Berkman, Glass, Brissette, and Seeman (2000) . Conversely, health selection operates if cognitive limitations affect quantity ( Aartsen, van Tilburg, Smits, & Knipscheer, 2004 ) and quality ( Gurung, Taylor, & Seeman, 2003 ) of social relationships, due to reduced social functioning ( Washburn, Sands, & Walton, 2003 ) and diminished social reciprocity ( Lang, Wagner, & Neyer, 2009 ). The direction of health selection effect is unclear.…”
mentioning
confidence: 99%
“…There have only been two studies that examined the direct relationship between ToM and social relations in older adults. While one study found that nurses ratings' of nursing home residents' social functioning were predicted by their performance on a ToM task (Washburn, 2003), the other study found no relationship between ToM and pro social behaviors in healthy older adults living in the community (Washburn et at, 2003;.…”
Section: Theory Of Mindmentioning
confidence: 97%